A life-cycle approach to food and nutrition security in India. Issue 5 (27th May 2014) - Rai, Rajesh Kumar; Kumar, Sandhya; Sekher, Madhushree; Pritchard, Bill; Rammohan, Anu
Abstract: India's poor performance on critical food and nutrition security indicators despite substantial economic prosperity has been widely documented. These failings not only hamper national progress, but also contribute significantly to the global undernourished population, particularly children. While the recently passed National Food Security Act 2013 adopts a life-cycle approach to expand coverage of subsidized food grains to the most vulnerable households and address food security, there remains much to be desired in the legislation. Access to adequate food for 1·24 billion people is a multifaceted problem requiring an interconnected set of policy measures to tackle the various factors affecting food and nutrition security in India. In the present opinion paper, we discuss a fivefold strategy that incorporates a life-cycle approach, spanning reproductive health, bolstering citizen participation in existing national programmes, empowering women, advancing agriculture and better monitoring the Public Distribution System in order to fill the gaps in both access and adequacy of food and nutrition.